Cognitive Control and Flexibility to Happiness: Distress Tolerance and Difficulties in Emotion Regulation as Serial Mediators - Satıcı, Seydi Ahmet; ÖZTÜRK, MELTEM; Okur, Sinan; Deniz, M. Engin (Springer, 2024)
Happiness is a positive construct that includes individual, interrelated cognitive and emotional components and is the pursuit of human nature. In this study, serial multiple mediation analysis was performed to test the hypothetical model that addresses distress tolerance and difficulties in emotion regulation as serial mediators in the relationship between cognitive control and flexibility, and happiness. The participants were 315 Turkish individuals from 34 cities in Turkiye. The structural equation modeling revealed that both distress tolerance and difficulties in emotion regulation have a full serial mediator role in the relationships between cognitive control and flexibility, and happiness. Limitations and future research suggestions are discussed.
Keywords: Cognitive Control and Flexibility; Distress Tolerance; Difficulties in Emotion Regulation; Happiness